Implementasi Bahan Ajar Persamaan Diferensial dengan Metode Guided Discovery Berbantuan Software Mathematica untuk Meningkatkan Pemahaman Konsep - Desty Haswati; Dian Nopitasari (Jurnal Gantang, 2019)
This study aims to examine the increase in student’s mathematical conceptual understanding ability using differential equation teaching materials using Guided Discovery assisted by Mathematica software. This study is a quasi-experimental with pretest posttest Control Group Design. The research subjects were the sixth semester students of Mathematics Education Study Program, Muhammadiyah University of Tangerang, with a sample of as many as two classes selected by simple random sampling technique. The experimental class uses differential equation teaching materials with the Guided Discovery method assisted by Mathematica software and the control class using ordinary teaching materials. The results of the study showed that an increase in mathematical conceptual understanding ability of the experimental class was higher than the control class. The average normalized gain of students in the experimental class is in the high and medium categories. While the control class is in the medium and low category. The normalized gain difference in the experimental class is better than the control class.